IMPLEMENTATION OF AN OBSTACLE AVOIDANCE ROBOT FOR SURVEILLANCE - Babatunde O Ayobami; Monday F. Ohemu; Alex Aligbe; Opeyemi O Adekogba; Zuleihat O. Zubair (International Journal of Innovations in Engineering Research and Technology, 2023)
This project is aimed at implementing an obstacle avoidance robot using ultrasonic sensor mounted on a servo motor for its movement and navigation without damaging itself. Atmega 328P microcontroller is used to achieve the desired operation and Arduino software was used to carry out the programming. The word “Robot” simply means any man-made machine that can perform work or other actions normally done by humans, either automatically or by remote control. Robotics is the blend of computational intelligence and physical machines (motors). In this project differential drive method will be used as the obstacle avoidance algorithm and the algorithm is implemented in the main microcontroller which is on the mobile robot. The Algorithm implemented is used to avoid the obstacle and to drive the robot to a locally generated goal. The use of servomotor provides great precision rotation as a scanner mechanism for the ultrasonic sensor. This autonomous robot, successfully maneuvered in any given environment without collision, the hardware used in this project is commonly available and inexpensive which makes the robot easily replicable.